Top management team and board of directors' temporal focus and strategic change: an empirical study - Ferrer, Fernanda Goulart (2020)
Top managers’ influence on strategic change has been widely addressed in the literature. There are plenty of findings that indicate the relevant role of cognition and behavioral responsibility in the decision-making process, lending credence to the bounded rationality theory. Researchers have dedicated special attention to the role of the CEO and the Top Management Team in strategic change initiation due to the fact that they are directly connected to the decision-making process. Grounded in the Upper Echelon theory and in the managerial cognition literature, the purpose of this study was to investigate how a particular filter, the temporal focus, serves as a mechanism that influences the decision-making of Top Management Teams and the Board of Directors and, consequently, the strategic change. This study adopts a qualitative approach based on a single case study and uses a broader perspective of the actors involved, including the role of Board of directors. Two main contributions were made to the Upper Echelon and strategic change theories: first, evidence of the influence of individuals’ temporal focus differences on the group’s dynamics and interactions in the decision-making process; second, a closer look at how top executives and Board of directors’ deliberation in decision-making and their interpretations influence the initiation of strategic change. This study can be of special interest for managers by calling their attention to subjective aspects of the decision-making process and helping them make better informed decisions.